Canadian Association of Gastroenterology Clinical Practice Guideline for the Medical Management of Pediatric Luminal Crohn's Disease. Issue 3 (10th July 2018) - Mack, David R; Benchimol, Eric I; Critch, Jeff; deBruyn, Jennifer; Tse, Frances; Moayyedi, Paul; Church, Peter; Deslandres, Colette; El-Matary, Wael; Huynh, Hien; Jantchou, Prévost; Lawrence, Sally; et al.
Abstract: Background & Aims: We aim to provide guidance for medical treatment of luminal Crohn's disease in children. Methods: We performed a systematic search of publication databases to identify studies of medical management of pediatric Crohn's disease. Quality of evidence and strength of recommendations were rated according to the GRADE (Grading of Recommendation Assessment, Development, and Evaluation) approach. We developed statements through an iterative online platform and then finalized and voted on them. Results: The consensus includes 25 statements focused on medical treatment options. Consensus was not reached, and no recommendations were made, for 14 additional statements, largely due to lack of evidence. The group suggested corticosteroid therapies (including budesonide for mild to moderate disease). The group suggested exclusive enteral nutrition for induction therapy and biologic tumor necrosis factor antagonists for induction and maintenance therapy at diagnosis or at early stages of severe disease, and for patients failed by steroid and immunosuppressant induction therapies. The group recommended against the use of oral 5-aminosalicylate for induction or maintenance therapy in patients with moderate disease, and recommended against thiopurines for induction therapy, corticosteroids for maintenance therapy, and cannabis in any role. The group was unable to clearly define the role of concomitant immunosuppressants during initiation therapy with a biologic agent, although thiopurine combinations are not recommended for male patients. No consensus was reached on the role of aminosalicylates in treatment of patients with mild disease, antibiotics or vedolizumab for induction or maintenance therapy, or methotrexate for induction therapy. Patients in clinical remission who are receiving immunomodulators should be assessed for mucosal healing within 1 year of treatment initiation. Conclusions: Evidence-based medical treatment of Crohn's disease in children is recommended, with thorough ongoing assessments to define treatment success.